6GHz 비면허 대역의 저전력 근접 무선통신과 기존 무선업무와의 공존 연구 - 김승남(Seung-Nam Kim); 이일규(Il-Kyoo Lee); 성주영(Joo-Young Sung) (한국정보통신학회논문지, 2021)
It has recently been noticed that the headway of unlicensed wireless technology is necessary as user's demands of wireless tech increase and the development of high-speed data service by using low-power short-range wireless network is needed. Hence, it is inevitable to study sharing and coexistence for broadband spectrum of diverse unlicensed application with wide bandwidth. In this paper, an interference examination between unlicensed WiFi (Wireless Fidelity) in the 6GHz and OB (Outside Broadcasting) system which is an incumbent service in the same frequency band was conducted and it suggests separation distance for the coexistence. Thus, MCL (Minimum Coupling Loss) and MC (Monte Carlo) methods were used to set up interference scenarios for the interference analysis and compute the separation distance between two systems according to the same frequency band and frequency separation. 최근 무선통신 사용자들의 기술 요구사항과 고속 데이터 기술 개발의 필요성이 증가되면서 비면허 무선접속 기술 개발이 주목되고 있다. 더 높은 주파수와 더 넓은 대역폭을 가진 WiFi (Wireless Fidelity)와 같은 저전력 근접 무선통신 서비스와 더불어 광범위한 비면허 기술의 응용성을 위해 다양한 주파수 대역에서의 스펙트럼 공존 및 공유 연구가 필수적이다. 본 논문에서는 지하철 내의 6GHz 비면허 대역의 WiFi와 기존 무선업무인 이동방송중계 시스템간의 간섭의 정도를 평가하고 공존을 위한 두 서비스간의 이격거리를 제안한다. 간섭 평가를 위해 최소결합손실 (MCL: Minimum Coupling Loss)방법과 몬테카를로 (MC: Monte Carlo)방법 기반의 간섭 시나리오를 설정하였으며, 두 시스템간의 동 대역과 주파수 이격에 따른 이격거리를 도출하였다.